Improving Public Investment Literacy through Digital Technology-Based Futures Trading Education: Peningkatan Literasi Investasi Masyarakat melalui Edukasi Trading Futures Berbasis Teknologi Digital - Ammara Putri Ainayah; Supriyono (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
In the era of globalization and the development of digital technology, an individual's ability to plan and manage finances is crucial to achieving financial well-being. Low financial literacy makes it difficult for people to make the right financial decisions, including choosing the right investment instrument. One of the fastest-growing instruments today is futures trading, which offers the potential for high returns but also comes with great risks. To answer this challenge, digital technology-based educational activities such as webinars effectively improve public investment literacy. This community service activity aims to provide an in-depth understanding of the mechanisms, potential, and risks of futures trading, and encourage people to be more aware and wise in investing. Through an interactive and accessible educational approach, it is hoped that the community can avoid illegal investments and be able to contribute to creating a healthy and inclusive financial market.